Programa de intervención de resiliencia en el personal militar de una institución armada del Perú, que integra unidades operativas desplegadas en zonas de emergencia - Ayala Robles, Patty Ysabel (2016)
The psychological advances in the last decades have contributed to the development of the positive mental health model of our country, since they have confronted the needs of the populations that demanded them, such is the case of the military professionals who, in fulfillment of their work of high active risk and directly in the frontal fight against the elements terrorists made possible the achievement of its objectives during its military operations; Therefore, in response to this problem, defense strategies have been established, incorporating resilience training programs. For the above, in the present investigation we intend to determine the influence of the application of a resilience intervention program of the military personnel, who integrated operative units of an Armed Institution of Peru, deployed in emergency zones. This research used an experimental design methodology, of a longitudinal type, with a sample composed of 261 of a population of 2088 military personnel, having 70 in the experimental group and 191 participants in the control group, applying the resilience test in two times, entry and exit, for the measurement of effectiveness of said Program, whose results were presented the respective analysis, sustaining its positive influence, evidencing improvements in said personnel, in aspects such as introspection, independence, interaction, creativity, morality and sense of humor; And it was recommended to replicate the theoretical practical research to samples of different socio cultural context, of bigger size and of diverse areas of work that ratify the efficiency of the program.